An Overview of Insurance Services in Nepal - Sharma, Puspa Raj (Janapriya Journal of Interdisciplinary Studies, 2017)
The present scenario of micro (finance and insurance) seems a lot of uncertainty. Naturally uncertainty gives birth to risk. Therefore, the need for risk-management solutions is undisputed by policy makers, who are aware that poor families can lose - in a matter of hours - assets that took years to accumulate, due to a sudden sickness or accident. The policy to provide free primary care and to a certain degree secondary care is positive step and could effectively help to reduce financial exposure of Nepal’s poor when the policy is implemented and functional on large scale. But even if this would succeed, only a part of the vulnerability is reduced: the poor still have to pay for services not covered under this policy, such as certain hospitalization cases, the transportation to health care providers, wage-loss – to name a few. The poor households currently need to finance huge amounts of health expenses (out of pocket expenditure) which are over and above their current income(s) and savings. They therefore need to resort to multiple sources of financing, of which a major source is borrowing. At present, there are 25 registered insurance companies in Nepal. Of these, 8 are private commercial life insurers, 16 are private commercial non-life insurers and 1 is composite insurer, i.e., Rastriya Beema Sansthan owned by the government. Janapriya Journal of Interdisciplinary Studies Vol. 2, No.1 (December 2013), page: 12-20